Allometric scaling of faunal-mediated ecosystem functioning: A case study on two bioturbators in contrasting sediments. (5th June 2021) - Fang, Xiaoyu; Moens, Tom; Knights, Antony; Soetaert, Karline; Van Colen, Carl
Abstract: Soft-sediment biogeochemistry is influenced by the bioturbation activity of benthic invertebrates. We investigated whether the effect of two macrobenthos bioturbators, Limecola balthica and Hediste diversicolor, on sediment oxygen uptake can be described by allometric principles of metabolic activity scaling with animal body size and population biomass. Microcosms containing reconstructed populations to control density and individual body size were used to compare bioturbation effects and allometric scaling principles between a sandy and muddy sediment. Both species facilitated oxygen uptake in both sediment types, and a major portion of the variance in sediment metabolism (60–98%) could be explained by the per capita body size and density, and total population biomass. The allometric relationship with the stimulated sediment metabolism was similar in sand and mud for Hediste and strongly related to the increasing burrow ventilation rate with population biomass. Limecola irrigated less in mud but stimulated sediment metabolism more in mud in comparison to in sand. We discuss how physico-chemical differences between both sediment types, possible changes in activity, and size-dependent irrigation dynamics can explain the variable effects of Limecola on sediment metabolism. Overall, we provide empirical evidence that allometric laws can be used to upscale bioturbation effects on ecosystem functioning in marine soft sediments from the individual to the population level. Graphical abstract: Image 1 Highlights: Allometric scaling predicts faunal population effects on seafloor metabolism. Stimulatory effects on sediment metabolism depend on species bioturbation traits. Stimulatory faunal effects on sediment metabolism can vary between sand and mud. Bio-irrigation effects on seafloor metabolism depend on species and sediment type.